A Comprehensive Literature Review of Anxiety and Depression in Youth With Chronic Pain - Putu Rizky, Putu Rizky; Syifa, Syifa; Irham Arif, Irham Arif (International Medical Journal Corp. Ltd, 2024)
Background: The literature on anxiety and depression in youth with chronic pain illustrates a multifaceted relationship between psychological and physiological factors that significantly affect the quality of life and functioning of affected individuals. High levels of anxiety have been consistently linked to poor functional outcomes in adolescents, regardless of pain intensity, suggesting that psychological factors, particularly anxiety, serve as critical moderators in the relationship between chronic pain and disability. Literature Review: This cyclical pattern of anxiety and depression exacerbating avoidance behaviors leads to increased physical and social impairment, highlighting the importance of addressing psychological health in chronic pain populations. The prevalence of anxiety disorders among youth with chronic illnesses, particularly chronic pain, is notably higher than in their healthy peers, emphasizing the psychological risks accompanying physical health issues (Tran, 2014). Anxiety often precedes chronic pain conditions, suggesting a temporal relationship where anxiety may not only contribute to the onset of chronic pain but also its maintenance (N. McKillop & A. Banez, 2016). Furthermore, the significant rates of mood disorders among young adults with chronic pain necessitate an understanding of the unique challenges faced by this demographic and the potential for technology-based interventions to alleviate distress . The correlation between chronic pain and psychiatric symptoms, particularly the gender disparity observed in prevalence rates, underscores the multifaceted impact of chronic pain on psychological health. Conclusion: Collectively, the literature emphasizes the significant and often detrimental impact of anxiety and depression on youth with chronic pain. It advocates for an integrated treatment approach that considers both physical and psychological dimensions, highlighting the necessity for ongoing research to further elucidate the complexities of these intertwined conditions.